The Role of PPARs in Disease II - Wagner, Kay-Dietrich; Wagner, Nicole (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains the original articles and reviews compiled in the Special Issue "The Role of PPARs in Disease II" published in Cells. Nicole Wagner and Kay-Dietrich Wagner from the University Côte d'Azur served as the Guest Editors of this Special Issue and compiled the reprint.